2011
DOI: 10.1038/nature10434
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral education of the immune system by colonic commensal microbiota

Abstract: SummaryThe instruction of the immune system to be tolerant of self, thereby preventing autoimmunity, is facilitated by the education of T cells in a specialized organ, the thymus, where self-reactive cells are either eliminated or differentiated into tolerogenic Foxp3+ regulatory T(Treg) cells1. However, it is unknown whether T cells are also educated to be tolerant of foreign antigens, such as those from commensal bacteria, in order to prevent immunopathology such as inflammatory bowel disease2–4. Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
805
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 944 publications
(857 citation statements)
references
References 34 publications
26
805
3
4
Order By: Relevance
“…However, an important piece of knowledge was still missing: are these iTreg cells generated against self or foreign antigens derived from the commensal bacteria? The study by Lathrop et al [3] answered this question, showing that iTregs are indeed induced by TCR recognition of commensal antigens. In turn they suggest the intestine as the key organ for the induction of peripheral tolerance.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…However, an important piece of knowledge was still missing: are these iTreg cells generated against self or foreign antigens derived from the commensal bacteria? The study by Lathrop et al [3] answered this question, showing that iTregs are indeed induced by TCR recognition of commensal antigens. In turn they suggest the intestine as the key organ for the induction of peripheral tolerance.…”
mentioning
confidence: 86%
“…Based on these results one would expect that germ-free mice, which do not have bacteria in the intestine, have reduced numbers of Treg cells in the colon. However, this was not the case [3], and one possible explanation for this controversy would be that tTreg cells compensate for the paucity of iTreg cells in the colon of germ-free mice. In line with this hypothesis, the authors found that Treg cells in the colon of germ-free mice expressed higher levels of the transcription factor Helios, which is preferentially expressed by tTreg cells [4].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1 Recent findings indicate that under homeostatic conditions, such peripherally induced Tregs (pTregs) are of functional importance mainly at feto-maternal interfaces and for maintaining tolerance to food-and microbiota-derived antigens at mucosal sites. [2][3][4][5][6] In addition to differences in ontogeny, there is growing evidence that Tregs having undergone antigen-specific stimulation may differ significantly from their naive recirculating counterparts in terms of activation status, migratory potential, and regulatory function. 7,8 Together with the notion that Tregs having different origins or anatomical locations display distinct but specific gene expression profiles, 9 this has led to the discovery of different functional Treg subpopulations, termed ''effector'' Treg lineages.…”
Section: Introductionmentioning
confidence: 99%
“…La grande sensibilité de la SFB aux mécanismes de défense de l'hôte, qu'elle contribue à induire, garantit son innocuité, sa transformation sous forme de spores lui permettant de survivre, et d'assurer sa transmission verticale [30]. Au-delà des interactions locales, le microbiote influence profondé-ment les réponses innées et adaptatives de l'hôte en périphérie [5,35] et semble ainsi capable de préparer le système immunitaire à répondre efficacement aux pathogènes. Les mécanismes de ces effets en péri-phérie sont incomplètement élucidés, mais sont principalement attribués à la diffusion vers la périphérie de facteurs solubles dérivés des bactéries et de leur métabolisme [2,36,37].…”
Section: Référencesunclassified